Efficacy of Papain Gel—A Smart Alternative to Conventional Methods of Carious Dentin Removal: An In Vitro Study - Paras Angrish; Ashish Kamboj; Malay Mitra; Rahul Kaul; Dempsy MM Chengappa; Aarti Sharma (Journal of South Asian Association of Pediatric Dentistry)
Aim: The study was aimed at finding out the efficacy of the caries removal ability of a chemomechanical agent (papain gel) and comparing it with that of conventional slow-speed rotary carbide burs and mechanical hand excavators in deciduous extracted molars. Materials and methods: A total of 30 extracted teeth that were used for the present study were distributed equally among two major categories (15 each) by simple random sampling technique. The teeth were sectioned into two halves mesiodistally in a longitudinal plane through the center of the caries. In each category, the corresponding halves were sectioned off randomly but in equal numbers further into two groups as follows: Category 1: Group I hand excavators and group II carbide burs. Category 2: Group III hand excavator group and group IV Papacarie group. Parameters recorded included total time taken for caries removal and residual caries remaining using caries detection dye in each group and category, which were estimated and observed under a stereomicroscope (magnification 12.5×). The data was computed and statistically analyzed to find out and compare the efficacy of caries removal of three different methods used. Results: As per the critical difference (CD), the results of the study showed the caries removal mean time for group IV (Papacarie group) when compared to other groups was significantly higher (p < 0.01). Group II had a significantly lower mean time than the other groups (p < 0.01). Results also showed group II had a significantly lower mean area of residual caries than the other groups (p < 0.01). A significantly lower mean of residual caries was found in group IV than that in group I and group III (p < 0.05). Conclusion: From the results of this study, it was found that papain gel can be used as an effective alternative method compared to conventional methods for caries removal, especially in pediatric patients, owing to its lesser time commitment and better outcome.